Health care cost savings from Australian Poisons Information Centre advice for low risk exposure calls: SNAPSHOT 2. (2nd July 2020) - Huynh, Alanna; Cairns, Rose; Brown, Jared A.; Jan, Stephen; Robinson, Jeff; Lynch, Ann-Maree; Wylie, Carol; Buckley, Nicholas A.; Dawson, Andrew H.
Abstract: Introduction: To estimate cost savings from the Australian Poisons Information Centres (PIC) through reductions in unnecessary health resources following unintentional low toxicity poisonings. Methods: Two telephone surveys were conducted. The first to PIC callers over a one-week period about unintentional exposures where the callers' alternate course of action in the hypothetical situation in which the PIC did not exist was questioned. The second survey to determine the proportion of callers followed PIC advice. We estimated cost savings associated with instances where individuals acted on advice not to present to hospital, when they indicated they would have otherwise as well as savings from preventing unnecessarily utilisation of medical resources. Database records of unintentional poisonings from all Australian PICs for 2017 were used. Results: A total of 958 consecutive callers were surveyed. PIC advised 91% of callers to stay at home, remaining callers were referred to hospital (5%), to their GP (3%) or given other recommended management advice (1%). PIC advice was followed by 97.6% of callers. In PIC absence, 22% of callers who were advised to stay home would have presented to hospital (3% via ambulance), 8% would visit their General Practitioner (GP) and only 9% would stay at home. In 2017, PICs were called about 94, 913 unintentional poisonings; and PICs generated at least 10.1 million in annual savings. Conclusion: In 2017, PICs provided at least a three-fold return on investment for every dollar invested, demonstrating that PICs are a highly cost effective service.